PENGARUH LATIHAN MENENDANG BOLA KE GAWANG TERHADAP KETEPATAN PASSING PADA TIM SEPAK BOLA SMKN 5 PEKANBARU - sirait, ramsyuren putra; slamet, slamet; wijayanti, ni putu nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the problem in this research was that the accuracy of passing the SMKN 5 Pekanbaru players was still missing, as evidenced by various tests and official competitions, and this was one of the factors that caused the defeat. This type of research is a form of experimental research to see the effect of the form of training. The purpose of this research was to see the effect of training the ball on the goal against the accuracy of passing on the SMKN 5 Pekanbaru football team. The population in this research consisted of a team of  SMKN 5 Pekanbaru, with a total of 14 people. The sampling technique is the use of total sampling, whereby the total population is sample. Data collection techniques obtained from the pre-test and the post-test. The instrument in this research used the Test that kicks the ball using the inner leg as a tool to measure the accuracy of passing. The analysis was performed using the t test. Based on data analysis and discussion, the results of the Tcount were 6.67 and Ttabel were 1.761. Means Tcount> Ttable, At the level of α= 0.05. It can then be concluded that there is a significant influence from the practice of looking the ball at the goal of the Pekanbaru SMKN 5 team. Key Words: Kick the ball into the goal, accuracy of passing